유기성 폐자원의 최종생분해도 및 다중 분해속도 평가 - 김선우(Sun Woo Kim); 강호(Ho Kang); 정지현(Ji Hyun Jeong) (Daehan hwan'gyeong gonghag hoeji, 2015)
Anaerobic mesophilic batch test of several organic wastes were carried out by a graphical statistic analysis (GSA) to evaluate their ultimate biodegradability and two distinctive decay rates ($k_1$ and $k_2$) with their corresponding degradable substrate fractions ($S_1$ and $S_2$). Each 3 L batch reactor was operated for more than 100 days at the substrate to inoculum ratio (S/I) of 0.5 as an initial total volatile solids (TVS) mass basis. Their Ultimate biodegradabilities were obtained respectively as follow; 69% swine waste, 45% dairy cow manure, 66% slaughterhouse waste, 79% food waste, 87% food waste leachate, 68% primary sludge and 39% waste activated sludge. The readily biodegradable fraction of 89% ($S_1$) of Swine Waste BVS ($S_o$) degraded with in the initial 31 days with $k_1$ of $0.116day^{-1}$, where as the rest 11% slowly biodegradable fraction ($S_2$) of BVS degraded for more than 100 days with the long term batch reaction rates ($k_2$) of $0.004day^{-1}$. For the Food Waste and Waste Activated Sludge, their readily biodegradable portions ($S_1$) appeared 89% and 80%, which degrades with $k_1$ of $0.195day^{-1}$ and $0.054day^{-1}$ for an initial 15 days and 28 days, respectively. Their corresponding long term batch reaction rates ($k_2$) were $0.003day^{-1}$ and $0.002day^{-1}$. Results from other organic wastes are addressed in this paper. The theoretical hydraulic retention times (HRTs) of anaerobic digesters treating organic wastes are easily determined by the analysis of multiple decay rate coefficients ($k_1$ and $k_2$) and their corresponding biodegradable substrate fractions ($S_1$ and $S_2$). 본 논문에서는 Graphical Statistic Analysis (GSA) 방법을 이용하여 유기성 폐자원의 최종생분해도와 다중 분해속도를 평가하였다. GSA에 의한 최종생분해도는 돈분뇨 69%, 젖소 생분뇨 45%, 도축폐기물 66%를 나타냈고 음식물류 폐기물과 음폐수는 각각 79%와 87%이었으며, 1차 슬러지와 폐활성 슬러지는 각각 68%와 39%이었다. 유기성 폐자원의 분해양상을 정확히 표현하기 위하여 사용된 다중분해속도해석(Multi k Analysis) 방법을 이용해 평가한 결과 돈분뇨는 $k_1$ ($0.116day^{-1}$)의 속도로 평균 31일 안에 전체 생분해성 유기물 중 빠르게 분해되는 분율($S_1$)인 89%가 분해되었으며, 느리게 분해되는 $S_2$의 분율은 11%로써 $k_2$ ($0.004day^{-1}$)의 속도로 남은 기간 동안 분해되었다. 젖소 생분뇨는 $k_1$ ($0.074day^{-1}$)의 속도로 평균 29일 안에 분해되었으며 $S_1$의 분율은 91%이었다. 도축폐기물과 1차 슬러지는 $k_1$ ($0.095day^{-1}$)의 같은 속도로 분해되었으며, $S_1$은 각각 89%와 85%를 보였다. 음식물류 폐기물과 음폐수는 15일의 운전기간 동안 $S_1$은 각각 89%와 93%로 기질의 대부분이 분해되었으며 $k_1$은 각각 $0.195^{-1}$과 $0.184^{-1}$로 대단히 빠른 속도로 분해되었다. 폐활성 슬러지는 $k_1$ ($0.054day^{-1}$)의 속도로 28일 동안 분해되었으며 $S_1$은 80%를 보였다. 따라서 Multi k Analysis 방법을 이용해 유기성 폐자원의 분해 속도와 분해 양상을 토대로 최소 HRT를 산정할 수 있으며, 본 대상시료를 활용한 바이오가스화 시설의 최적 설계인자 도출이 가능하다.